Investment specificity, vertical integration and market foreclosure - Frank Bickenbach; Iestyn Williams (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
In this paper we consider the impact of vertical integration on a retailer's choices of product variety and specific, brand-supporting investment. In an incomplete contract environment, vertical merger encourages investment in integrated supply, and foreclosure of non-integrated manufacturers. Anti-competitive as opposed to efficiency interpretations depend delicately on a trade-off between the benefits of supplier-specific rather than generally applicable retailer investment, and the value of multi-product rather than single product retailing. Where retailers compete, it is shown that vertical integration implements competition reducing, product differentiating investment strategies.
Keywords: L22; L12; L4; 330; incomplete contracts; vertical integration; monopolization; Vertikale Konzentration; Unvollständiger Vertrag; Einzelhandel; Sortiment; Wettbewerbstheorie; Wirtschaftliche Effizienz; Theorie